Knowledge, Anxiety, and Fear of the Unknown Among Pregnant Women During COVID-19 Pandemic - Shahla Khosravan; Fatemeh Mohammadzadeh; Elham Hassannia; Mozhgan Mansoorian; Zohreh Zamani; Narjes Bahri (Journal of Research & Health, 2022)
Background: This study aimed to determine pregnant women’s knowledge about COVID-19 and their anxiety and fear of the unknown. Methods: This online cross-sectional study was conducted in March and April 2020 on Iranian pregnant women visiting comprehensive healthcare centers affiliated with the Gonabad University of Medical Sciences. Participants were selected using a stratified random sampling strategy among pregnant women who agreed to participate, had a Telegram or WhatsApp account or phone number, and had no history of pregnancy complications. A demographic questionnaire, Spielberger’s state-trait anxiety inventory, fearing the unknown questionnaire, and an uncertainty scale was used to collect data. Data were analyzed using simple and multiple linear regression models using SPSS software, version 16. Results: A total of 190 pregnant women were included in the analysis. The Mean±SD for knowledge of COVID-19 was 8.82±1.72. The knowledge of 71.1% of participants was moderate. The Mean±SD for fearing the unknown was 36.2±9.1. The Mean±SD for the state anxiety about COVID-19 incidence in pregnant women was 47.6±10.2. The results showed that 65.3% of the participants had a moderate level of anxiety. Multiple regression analysis showed an increase of 0.16 (P=0.029) in the fearing the unknown score for each week of increase in the gestational age. Similarly, the anxiety increased by 0.56 (P<0.001) for each unit of increase in fearing the unknown. Moreover, the results showed that the anxiety of people using Telegram or WhatsApp was 3.44 units more than others (P<0.018) Conclusion: The findings showed that the pregnant women’s knowledge was moderate at the time of research. However, with increasing gestational age, fear of the unknown, and sources of knowledge were associated with anxiety. This points to the essentiality of increasing supportive programs and it is required to screen pregnant women to prevent the adverse effects of anxiety.